(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This research aims to demonstrate the most important foundations to the Marxist material philosophy as German philosophy, especially the philosophy of Hegel, the theories of French socialism, and the theories of English economic and political in the 19th century, Marx enabled by that foundations to forming the dialectical material method as an effective tool for understanding and interpreting history scientifically by showing the importance of human work and social production as an infrastructure that reflects manifestations of the human existence, social, political, and cultural institutions. The Marxist material philosophy differs from the materialism and idealism philosophies which before it of method and doctrine, The method became an ideological tool for liberating the poor from the social oppression which practiced by the ruling classes and the owners of the tool of production throughout history, and the research will try to clarify it by linking the theoretical assets of Marxism with their actual applications, in addition to demonstration the reasons of success and failure in the application.